1991
DOI: 10.1002/int.4550060704
|View full text |Cite
|
Sign up to set email alerts
|

A self-organizing pattern retrieval system and its applications

Abstract: This article is an overview of research on the design and application of a Self-organizing Pattern Retrieval System. This system is a nontraditional form of database for several reasons: (1) The objects (patterns) stored in the database are complex data structures such as graphs, or matrices as opposed to relations, sets, lists or frames; (2) the system attempts to optimize its internal structure for retrieval efficiency by taking advantage of classificatory information (common patterns) it discovers about the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Another feature of concept lattices is that they can generate overlapping classes. Although this is not a new idea (e.g., Levinson, 1984;Lebowitz, 1986) the importance of this issue has been somewhat overlooked. On one hand, very little work has been done on acquiring formally characterizable classes of partially ordered sets of clusters;…”
Section: Related Work On Clustering and Browsingmentioning
confidence: 99%
“…Another feature of concept lattices is that they can generate overlapping classes. Although this is not a new idea (e.g., Levinson, 1984;Lebowitz, 1986) the importance of this issue has been somewhat overlooked. On one hand, very little work has been done on acquiring formally characterizable classes of partially ordered sets of clusters;…”
Section: Related Work On Clustering and Browsingmentioning
confidence: 99%
“…Background knowledge can take the form of known substructure models that may potentially appear in the database or graph match rules to adjust the cost of each inexact graph match test. Unlike other existing approaches to graph-based discovery [5,19,25,28,28], Subdue is effective at finding interesting and repetitive substructures in any structural database with or without domain-specific guidance. The results of the scalability study in Section 3 are demonstrated on databases in two different domains.…”
Section: Overview Of Subduementioning
confidence: 99%
“…Although this is not a new idea (e.g. (Levinson, 1984;Lebowitz, 1986)) the importance of this issue has been somewhat overlooked. On one hand, very little work has been done on acquiring formally characterizable classes of partially ordered sets of clusters; on the other hand, although learning overlapping classes may be an important practical requirement even for pure predictive tasks (Martin & Billman, 1994), data sets with non-disjoint classes have been surprisingly rare in the machine learning literature.…”
Section: Related Work On Clustering and Browsingmentioning
confidence: 99%